Penerapan Contextual Teaching and Learning (CTL) untuk Meningkatkan Hasil Belajar Matematika tentang Kesetaraan Nilai Uang - Djuariah Djuariah (Tunas Nusantara, 2022)
AbstractThe Mathematic learning outcomes on low level has caused bye several factors, such as the non-contextual books appearances, the teachers have lack of competencies and students’ understanding as scary subject.The purpose of this research is to enhance the Mathematic learning outcomes about the equality of the money value through the application of Contextual Teaching and Learning (CTL). This Class Action Research (CAR) is going on the Third Class of Waru 3 General Elementary School. The subjects of this research are 31 students (17 boys and 14 girls). The applications of CTL are using the game money as the display tools and work sheet in group.The result of this research is learning outcomes enhanced. On the Pre Cycle, the learning outcomes are 56 for the average and 23% for the class completeness. On the First Cycle, the learning outcomes are 66 for the average and 52% for the class completeness. On the Second Cycle, the learning outcomes are 83 for the average and 94% for the class completeness. Abstract ______________________________________________________________The Mathematic learning outcomes on low level has caused bye several factors, such as the non-contextual books appearances, the teachers have lack of competencies and students’ understanding as scary subject.The purpose of this research is to enhance the Mathematic learning outcomes about the equality of the money value through the application of Contextual Teaching and Learning (CTL). This Class Action Research (CAR) is going on the Third Class of Waru 3 General Elementary School. The subjects of this research are 31 students (17 boys and 14 girls). The applications of CTL are using the game money as the display tools and work sheet in group.The result of this research is learning outcomes enhanced. On the Pre Cycle, the learning outcomes are 56 for the average and 23% for the class completeness. On the First Cycle, the learning outcomes are 66 for the average and 52% for the class completeness. On the Second Cycle, the learning outcomes are 83 for the average and 94% for the class completeness.Contextual Teaching and Learning, Learning Outcomes, Mathematic, Money  Kata Kunci: Contextual Teaching and Learning, Learning Outcomes, Mathematic, Money